СONCOMITANT ADMINISTRATION OF CLOPIDOGREL AND PROTON PUMP INHIBITORS: ARE THERE ANY OPEN QUESTIONS LEFT TODAY? - S. Yu. Martsevich; A. Yu. Suvorov (Столичная издательская компания, 2015)
Concomitant administration of clopidogrel and proton pump inhibitors (PPI), the possible influence of PPI on the effectiveness of clopidogrel often raises questions among practitioners. Massive antithrombotic therapy increases the risk of upper gastrointestinal tract lesions. Concomitant administration of these drugs is studied in a large number of trials. Results of the most significant of these trials are considered. Safety of concomitant administration of clopidogrel and PPI, its impact on long-term outcomes of cardiovascular diseases, and a choice of particular PPI are also discussed.